Are local anesthesia vials similar to champagne: Do they lose their potency once opened?: An in vitro study - P S Gopinath Thilak; Sameep S Shetty; Jagadeesh Chandra; Kavana Gowda (Wolters Kluwer Medknow Publications, 2017)
Background and Objectives: Epinephrine is volatile and unstable on exposure to air. Addition of sodium metabisulfite as an antioxidant has been effective, but there are no clear-cut consensus on its efficiency in retarding the oxidation that sets in once the anesthetic vials are kept open with a needle in situ. There is a paucity of scientific data regarding the risks of reuse of anesthetic vials following the use of cartridges, a common practice in western countries. It is our endeavor to shed light on the constant change in pH, drug deterioration, and instability that sets in an anesthetic vial with a needle in situ. Methods: Twenty sets of identical local anesthetic vials (lidocaine 2% with 1:80,000 adrenaline) were collected. The samples were divided into four individual groups followed by a segregation of 5 subsamples at varying time intervals from each individual group. pH was measured using pH meter. Results: Change in the pH of the solution was noted as days progressed in open local anesthetic vials when compared to closed vials. However, the decreased pH remained constant following a brief time interval after complete conversion of sulfite to sulfate. Conclusions: Local anesthetic vials with needle pricked in for a longer duration can alter the pH, concentration of the vasoconstrictor and deteriorate the properties of local anesthetic solution. This can manifest clinically as delayed onset of action, increased burning sensation, and pain on administration.